Identifikasi Taksa Tanah di Situs Megalitik Gunung Padang Kabupaten Cianjur - Mahfud Arifin; Ridha Hudaya; Apong Sandrawati; Muhammad Amir Solihin; Ganjar Herdiansyah (Soilrens, 2016)
Mount Padang was famous megalith sites placed in Cianjur District. Mani discipline of science studied Mount Padang sites in order to find out the truth of histories. Based on geological studies, Mount Padang sites constructed by andesitic rock, this argument need more fact for get the real data. This research aimed to analysis pedological proses in Mount Padang sites. The result of study was soil classification which description by soil profile. Based on result of reseach the soil in Mount Padang formed in Qv rock formation. The result of soil profile analized with 2 meters depth, there was 10 layer formed e.g Ap, AB, Bw1, Bw2, BC1, BC2, CB1, CB2, C1, and C1. The genesis of Mount Padang soil was in viril levels, due to molic epipedon and cambic that found as below horizon diagnostics. Based on soil taxonomy, this pedon were classified as Typic Dystrudepts.Key words: megalith sites, andesitics rock, soil profile, viril, cambic